2020
DOI: 10.1002/jccs.201900452
|View full text |Cite
|
Sign up to set email alerts
|

Novel [1,2,4]triazolo[3,4‐b][1,3,4]thiadiazine derivatives embedded with benzimidazole moiety as potent antioxidants

Abstract: Fourteen novel [1,2,4]triazolo[3,4‐b][1,3,4]thiadiazine derivatives bearing benzimidazole moiety (7a‐n) have been synthesized using the one‐pot nitro reductive cyclization method. All the synthesized compounds were confirmed by 1H nuclear magnetic resonance (1H NMR), 13C NMR, fourier‐transform infrared (FT‐IR), mass spectrum, and elemental analyses. All the title compounds were subjected to in vitro antioxidant activity. The free radical scavenging activity of the compounds was examined using DPPH, nitric oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Sathyanarayana et al [ 113 ] designed and synthesized benzimidazole linked 1,2,4-triazolo[3,4- b ][1,3,4]thiadiazine derivatives ( 146 ) and assessed their in vitro antioxidant potential using DPPH, nitric oxide and superoxide radical scavenging methods. Among them, compound 146c showed more activity in both DPPH and nitric oxide radical assay, with IC 50 values of 13.57 and 18.55 μg ml −1 compared with standard (IC 50 = 23.75 and 23.14 μg ml −1 , respectively).…”
Section: Pharmacological Properties Of 124-triazolo[34- B ][134]thiadiazinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sathyanarayana et al [ 113 ] designed and synthesized benzimidazole linked 1,2,4-triazolo[3,4- b ][1,3,4]thiadiazine derivatives ( 146 ) and assessed their in vitro antioxidant potential using DPPH, nitric oxide and superoxide radical scavenging methods. Among them, compound 146c showed more activity in both DPPH and nitric oxide radical assay, with IC 50 values of 13.57 and 18.55 μg ml −1 compared with standard (IC 50 = 23.75 and 23.14 μg ml −1 , respectively).…”
Section: Pharmacological Properties Of 124-triazolo[34- B ][134]thiadiazinesmentioning
confidence: 99%
“…Sathyanarayana et al [ 113 ] reported that novel [1,2,4]triazolo[3,4- b ][1,3,4]thiadiazine derivatives 146 bearing benzimidazole moiety obeyed most of the ADME parameters. Most of these compounds showed TPSA < 80 Å 2 , indicating their good intestinal absorption.…”
Section: Pharmacokinetic Profilementioning
confidence: 99%
“…Meanwhile, thiadiazine‐based compounds have attracted significant interest as shown in Figure 1, due to their wide‐applicability as biologically active compounds [6,7] . Their moiety was reported to exhibit anticancer, anti‐coronavirus, [8] anti‐bacterial, [9] anti‐HIV, [10] and antioxidant activities [11] …”
Section: Introductionmentioning
confidence: 99%